Urinary Nephrin is a Sensitive Marker to Predict Early Onset of Nephropathy in Type 2 Diabetes Mellitus - Veluri, Ganesh; Mannangatti, Murugan (Journal of Laboratory Physicians, 2022)
Objective The present study has been designed to evaluate urinary nephrin that best predicts the occurrence of renal dysfunction in type 2 diabetes mellitus patients and its correlation with clinical parameters of nephropathy.Materials and Methods A total of 80 type 2 diabetes mellitus and 40 age- and gender-matched healthy controls were recruited. Biochemical and clinical parameters were analyzed in all the study participants. Analysis of variance was performed to compare the differences between the groups. Pearson's correlation analysis was used to analyze the association of nephrin with clinical parameters of nephropathy. Receiver operating characteristic curves were constructed to study the diagnostic accuracy of markers to identify diabetic nephropathy.Results The levels of nephrin were significantly elevated in both groups of type 2 diabetes mellitus patients when compared with healthy individuals (p = 0.0001). The urinary nephrin was positively correlated with hemoglobin A1c and urinary albumin creatinine ratio (r = 0.520, 0.657, p < 0.0001) and negatively correlated with estimated glomerular filtration rate (r = –0.539, p < 0.0001). The diagnostic sensitivity and specificity of nephrin for nephropathy were 100 and 88%, respectively, and urinary albumin creatinine ratio was 43 and 76%, respectively.Conclusion The study findings suggest that nephrin levels are strongly and positively associated with nephropathy in type 2 diabetes mellitus patients and it has a greater potential to be an early predictable marker of nephropathy than urinary albumin creatinine ratio.
Keywords: HbA1c; type 2 diabetes mellitus; urinary nephrin